KOMPETENSI GRAMATIKAL BAHASA JEPANG MAHASISWA TINGKAT III TAHUN AKADEMIK 2015/2016 FKIP-UNIVERSITAS RIAU - Yeinnta, Aira Minwa; Basri, Merri Silvia; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine how grammatical competence or knowledge of Japanese grammar in particular areas of syntax and semantics at third level students of academic year 2015/2016 and the factors that influence it. In this study, the method used is descriptive method with quantitative approach and data was collected through tests and questionnaires. Results of tests and questionnaires are calculated using a predetermined formula to determine the average and the percentage level of mastery the syntax and semantic aspects as well as the factors that influence it.Based on the calculation results of the test answers, it can be seen that the students have enough knowledge on the level of both the scope of competence of grammatical (syntactic-semantic) for elementary-secondary level. Counting results of the questionnaire answer indicate that there are several factors both internal factors and external factors are not functioning optimally in the process of learning Japanese grammatical.Keywords: grammatical competence, learning Japanese grammar (Bunpou).